2018
DOI: 10.1002/ecy.2420
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity and density predict belowground diversity and function in an early successional alpine ecosystem

Abstract: Despite decades of interest, few studies have provided evidence supporting theoretical expectations for coupled relationships between aboveground and belowground diversity and ecosystem functioning in non-manipulated natural ecosystems. We characterized plant species richness and density, soil bacterial, fungal and eukaryotic species richness and phylogenetic diversity (using 16S, ITS, and 18S gene sequencing), and ecosystem function (levels of soil C and N, and rates of microbial enzyme activities) along a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 61 publications
(127 reference statements)
5
67
3
Order By: Relevance
“…Among the variables reflecting the effects of vegetation, plant species richness has a particularly strong negative effect on bacterial diversity (Table S2). This result stands in contrast with previous studies that reported either a positive correlation between bacterial diversity and plant diversity in the Rocky Mountains in Colorado, USA (16) or a neutral relationship in global temperate grassland (15, 50). For clades with different functions, the diversity of most oligotrophic clades is negatively correlated with plant species richness, consistent with previous studies (43, 45).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Among the variables reflecting the effects of vegetation, plant species richness has a particularly strong negative effect on bacterial diversity (Table S2). This result stands in contrast with previous studies that reported either a positive correlation between bacterial diversity and plant diversity in the Rocky Mountains in Colorado, USA (16) or a neutral relationship in global temperate grassland (15, 50). For clades with different functions, the diversity of most oligotrophic clades is negatively correlated with plant species richness, consistent with previous studies (43, 45).…”
Section: Discussioncontrasting
confidence: 99%
“…For clades with different functions, the diversity of most oligotrophic clades is negatively correlated with plant species richness, consistent with previous studies (43, 45). In contrast, the diversity of most copiotrophic clades (such as Betaproteobacteria ) is positively correlated with plant species richness (Table S1) (16, 50). Those results further corroborate the dominance of oligotrophic bacterial clades in infertile grassland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We classified plots as early, mid, or late succession by running a PCA of environmental and plant variables previously determined to change over successional gradients in alpine areas (Bekku et al, 2004;Schmidt et al, 2008;Porazinska et al, 2018)…”
Section: Discussionmentioning
confidence: 99%
“…Microbes are important regulators of ecosystem function, and much research has been directed at testing how soil microbial composition and diversity shift along environmental gradients. Work, thus far, has identified many important abiotic and biotic drivers that structure the composition and diversity of microorganisms in the soil, including pH, salinity, climate, soil nutrients, plant diversity, and plant functional traits (Fierer and Jackson, 2006;Lozupone and Knight, 2007;Nemergut et al, 2010;de Vries et al, 2012;Porazinska et al, 2018). However, how interactions among microbial taxa change across the landscape is much less well understood (Nemergut et al, 2013).…”
Section: Introductionmentioning
confidence: 99%